Designing Smart Student Savings Tools Based on Arduino and Web (International Journal of Scientific Research and Management (IJSRM), 2020)
In this modern era, everything is done easily, from electronic equipment to electronic transactions is developed increasingly sophisticated. The equipment and sophisticated electronic transactions turned out to have major problems that could result in dissipation, especially students in schools. The purpose of this study is to create and design a smart savings machine tool, where this machine will be controlled via RFID and a sensor with a microcontroller, so that each individual can learn to economize in managing finances. This machine is designed by adding a color sensor for depositing and withdrawing cash with only three nominal banknotes, namely Rp. 10,000, Rp. 5,000 and Rp. 2,000. Furthermore, this device is also able to calculate the financial balance that has been entered. As an input, Arduino Mega 2560 is needed for data processing. Whereas, the color sensor output is used to read the basic colors red, green and blue on the surface of the lower left corner of the rupiah banknotes. This tool works as desired, can read RFID (Radio Frequency Identification) cards that have been determined and the color sensor can respond to colors on a nominal bill of Rp 2,000, Rp.5,000 or Rp. 10,000 and able to detect the time when saving and accumulating the balance. To attract money into the storage area, two DC motors are used. When the TCS230 color sensor detects money, there are several times that the currency is unreadable due to the influence of external light which causes the sensor to be inaccurate in reading the frequency value of the money color.